The glucocorticoid receptor in the nucleus accumbens plays a crucial role in social rank attainment in rodents. (February 2020) - Papilloud, Aurélie; Weger, Meltem; Bacq, Alexandre; Zalachoras, Ioannis; Hollis, Fiona; Larrieu, Thomas; Battivelli, Dorian; Grosse, Jocelyn; Zanoletti, Olivia; Parnaudeau, Sébastien; Tronche, François; Sandi, Carmen
Highlights: High anxious, submissive-prone rats show lower GR expression in the NAc. Viral downregulation of GR in the NAc in rats leads to improved social rank. Mice lacking GR in dopaminoceptive neurons exhibit more dominant behavior. Abstract: Social hierarchy in social species is usually established through competitive encounters with conspecifics. It determines the access to limited resources and, thus, leads to reduced fights among individuals within a group. Despite the known importance of social rank for health and well-being, the knowledge about the processes underlying rank attainment remains limited. Previous studies have highlighted the nucleus accumbens (NAc) as a key brain region in the attainment of social hierarchies in rodents. In addition, glucocorticoids and the glucocorticoid receptor (GR) have been implicated in the establishment of social hierarchies and social aversion. However, whether GR in the NAc is involved in social dominance is not yet known. To address this question, we first established that expression levels of GR in the NAc of high anxious, submissive-prone rats are lower than that of their low anxious, dominant-prone counterparts. Furthermore, virally-induced downregulation of GR expression in the NAc in rats led to an improvement of social dominance rank. We found a similar result in a cell-specific mouse model lacking GR in dopaminoceptive neurons (i.e., neurons containing dopamine receptors). Indeed, when cohabitating in dyads of mixed genotypes, mice deficient for GR in dopaminoceptive neurons had a higher probability to become dominant than wild-type mice. Overall, our results highlight GR in the NAc and in dopaminoceptive neurons as an important regulator of social rank attainment.